Gatesville-Siding, Clay County - Schnee, Angela (Kansas State University, The Chapman Center for Rural Studies, 2011)
Gatesville was named for Lorenzo Gates, who settled on Mall Creek in the fall of 1857. There was a school, a post office, and a railroad, but no town was ever established, even though it was an essential hub for livestock shipping.
Angela Schnee, “Gatesville-Siding, Clay County,” Chapman Center Research Collections, https://ccrsresearchcollections.omeka.net/items/show/19.
Keywords: Clay County; Gatesville; Mall Creek; Milford Reservoir; Republican River; Siding